2014
DOI: 10.15590/abcjar/2014/v3i2/54976
|View full text |Cite
|
Sign up to set email alerts
|

Impacts of Corporate Social Responsibility on Customer Satisfaction in Telecom Industry of Bangladesh

Abstract: Worldwide interest is growing day by day about corporate social responsibility (CSR). In the light of the fact stated just now, this paper symbolizes on how customer satisfaction and loyalty are influenced by CSR factors. This paper has investigated the effects of service quality and consumer satisfaction along with corporate social responsibility actions on consumer purchase intentions and further on consumer loyalty. This research was based on primary and secondary data with some structured questionnaire. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…CSR plays various roles on community development: (1) sharing the negative outcome on the community because of industrialization, (2) make a closer connection between the community and the organizations, (3) help in finding ability inside the networks, and (4) help in shielding the networks from environmental consequences (Ismail, 2009). Various studies found that CSR has contribution in community development and customer satisfaction (Alam & Rubel, 2014;Eweje, 2006;Ismail, 2009;Shin & Thai, 2015). As HR is critical factor of business process, it is additionally positioned to upgrade the process of CSR (Strandberg, 2009).…”
Section: Hypotheses Developmentmentioning
confidence: 99%
“…CSR plays various roles on community development: (1) sharing the negative outcome on the community because of industrialization, (2) make a closer connection between the community and the organizations, (3) help in finding ability inside the networks, and (4) help in shielding the networks from environmental consequences (Ismail, 2009). Various studies found that CSR has contribution in community development and customer satisfaction (Alam & Rubel, 2014;Eweje, 2006;Ismail, 2009;Shin & Thai, 2015). As HR is critical factor of business process, it is additionally positioned to upgrade the process of CSR (Strandberg, 2009).…”
Section: Hypotheses Developmentmentioning
confidence: 99%
“…There is no proportional correlation between execution of economic responsibility and customer satisfaction/ corporate reputation; instead, this is regarded as the basic responsibility of companies. The study of Alam and Rubel (2014) find there is no relationship between awareness of CSR and purchase intention. Moreover, there is no relationship between customer satisfaction and purchase intention, nor purchase intention and consumer retention for the telecommunications industry of Bangladesh.…”
Section: Customer Satisfactionmentioning
confidence: 92%